Mycenaean Pefkakia Excavation Project: preliminary report on archaeological research conducted in 2023 - Bartłomiej Lis; Anthi Batziou; Łukasz Miechowicz; Piotr Zeman; Dominika Kofel-Lubczyńska; Vasiliki Tzevelekidi; Rena Veropoulidou; Dimitris Agnousiotis (Polish Archaeology in the Mediterranean)
This is a report on the second season of a five-year (2022–2026) archaeological project at the site of Mycenaean Pefkakia, which is a collaboration between the Polish Archaeological Institute at Athens and the Ephorate of Antiquities of Magnesia. In 2023, following an extensive geophysical survey and geoarchaeological corings conducted during the previous season, two trenches were opened in sectors designated as B and C. In Sector B, a burial ground from the late Hellenistic–Roman period was found, and several amphora burials as well as a single tile grave were excavated. However, layers dating to the Late Helladic (LH) period have not been revealed, despite a significant depth reached. In Sector C, stone walls of a multi-phase building dated to LH IIIA2 were found. In addition, traces of continued habitation past 1200 BC in the area were attested by pottery fragments from the more developed LH IIIC period.